Exploring In-Class Writing Activities in Teacher Education: A Study of Perspectives on Writing in Literacy Events - Ingunn Ofte; Kristin Solli (Nordic Journal of Literacy Research, 2024)
Writing is a central yet under-researched activity in teacher education classrooms. In this study, we explore in-class writing activities used by a multidisciplinary group of teacher educators at one teacher education institution. The purpose is to gain a better understanding of the nature of the writing activities and perspectives on writing they reflect. To this end, we analyze writing prompts and fieldnotes from classroom observations of fifteen literacy events in which writing was at the center. While our analysis reveals multiple and overlapping perspectives on writing, it also shows that writing activities are understood primarily as versatile learning tools. This is reflected in a focus on cross-disciplinary uses of writing to enhance students’ content learning, rather than on explicit development of discipline-specific writing conventions. Furthermore, our analysis shows that there is limited metacommunication about the writing that takes place in the literacy events. We suggest that there is untapped potential among these teacher educators when it comes to making the pedagogical rationales behind the use of in-class writing activities explicit to the students. Such explicit rationales might support students in developing a greater understanding of how to use and work with writing as future teachers.